Exploring the role of pharmacy students using entrustable professional activities to complete medication histories and deliver patient counselling services in secondary care - Adam Pattison Rathbone; Charlotte Lucy Richardson; Amy Mundell; Wing Man Lau; Hamde Nazar (Elsevier, 2021)
Entrustable professional activities (EPAs) allow tasks to be delegated to trainees. A new model of pharmacy placements was developed that used EPAs to appropriately supervise students providing patient counselling for inhalers, anticoagulation and simple analgesia at a tertiary care hospital. Students were provided with clinical communication training (e.g. how to do the counselling) as well as mandatory occupational training (e.g. fire safety). Data was collected (by students and placement facilitators) relating to the number of consultations (n = 1361) and patients who received counselling (n = 308) carried out by students (n = 71) over a 20 week period. Students documented these consultations, recording information such as the patient identification details, subjective and objective history, their assessment of the patients' need, as well as any action taken and any further planned action that was required. These notes were analysed using a Quality and Utility Assessment Framework by three clinical pharmacists. Data was analysed using simple descriptive statistical analysis on Microsoft Excel. Documentation was deemed High Quality (41%), Medium Quality (35%) and Low Quality (24%). The results indicate that pharmacy students can use entrustable professional activities to contribute to clinical services, completing high-quality patient consultations that have utility in clinical practice. Further work is needed to evaluate impact on clinical service delivery and establish the educational utility of using EPAs to support the pharmacy workforce to develop their consultation skills.